Lignin monomeric composition of corks from the barks of Betula pendula, Quercus suber and Quercus cerris determined by Py–GC–MS/FID (Journal of Analytical and Applied Pyrolysis, 2012)
Samples of cork tissues separated from the barks of Betula pendula, Quercus suber and Quercus cerris were characterized by Py–GC–MS/FID in respect to composition of lignin. The pyrolysis temperature influenced the yield of pyrolysis products, and in the conditions usually applied to wood pyrolysis (550 ◦C) suberin is only partially degraded into products. The lignin composition of the three corks showed predominantly a guaiacyl-based lignin: guaiacyl (G) units represented 85.7%, 96.4% and 93.7% of lignin respectively in B. pendula, Q. suber and Q. cerris corks, while syringyl (S) units amounted respectively to 11.9%, 2.5% and 2.7% and p-hydroxyphenyl (H) units to 2.4%, 1.1% and 3.6%. Pyrolysis of the woods of these same species confirmed the GS character of their lignins in contrast to the corks G-lignin type. The influence of ferulic acid in the results and its integration in a heterogeneous cork lignin structure was discussed.